Mapping Rare Erythrocyte Phenotypes in Morocco: A Tool to Overcome Transfusion Challenges. (12th March 2014) - Benahadi, A.; Boulahdid, S.; Adouani, B.; Laouina, A.; Mokhtari, A.; Soulaymani, A.; Hajjout, K.; Benajiba, M.; Alami, R.
Abstract : The aim of this research is to search for the distribution of blood groups in all the regions of Morocco. This study, done for the first time, aimed to provide the frequency of the Rhesus system and Kell (K) in more than 55000 blood donors from nine different regions around the country. In addition, the frequency of the Cellano, Duffy, Kidd, and MNS blood antigens was searched for 500 blood donors from the Rabat's region. Frequency of blood donors with rare blood groups was characterized for the first time in the country and compared to results found from other populations.